Quantitative determination of rofecoxib in pharmaceutical preparations - (:unkn) unknown (GOVI-VERLAG GMBH, 2004)
Rofecoxib was assayed by UV spectrophotometry and HPLC, the concentration ranges were 2-30 mug (.) ml(-1) and 5-50 mug (.) ml(-1), respectively. The results, obtained by the two methods in pharmaceutical preparations were compared of each other. There were no significant differences between the mean values and the precisions.
Keywords: PERFORMANCE LIQUID-CHROMATOGRAPHY; POSTCOLUMN PHOTOCHEMICAL DERIVATIZATION; SOLID-PHASE EXTRACTION; HUMAN PLASMA; FLUORESCENCE DETECTION; INHIBITOR